Tabu Search Embedded Simulated Annealing for the Shortest Route Cut and Fill Problem - LIM, Andrew (Institutional Knowledge at Singapore Management University, 2005)
The shortest route cut and fill problem proposed by Henderson et al is studied in this paper where we extend the model to include multiple vehicles and a makespan objective. A new tabu search embedded simulated annealing algorithm for both models is developed. Computational experiments show that the new approach is robust and achieves better solutions when compared with those found using Henderson et al's algorithm for larger test cases within significantly shorter times.